Shifting Learning Atmosphere through Process Drama: Teaching English Parts-of-Speech (PoS) in Indian Classroom - Mahant P.K.; Alam S.; Ghosh S.; Jabeen I. (My University, 2025)
This paper investigates the effectiveness of process drama in teaching English parts-of-speech to middle school students in an eastern Indian school. For the application part, researchers developed process drama-based lesson plans following the structural approach and implemented them among the students of class VII studying English as a second language (L2). The study employed a quasi-experimental design, with a pretest-posttest approach to data collection. Additionally, the facilitator consistently took observational field notes to understand the utility and limitations of process drama in a second-language classroom. The study's major findings indicate a significant growth in the treatment group and showed seminal benefits over the traditional method of teaching parts-of-speech through the structural approach. Moreover, observation and field notes indicated the welcoming attitude of learners towards process drama-based language pedagogy. Also, observation and field notes showed assistance in understanding the utility and limitations of process drama as a pedagogical tool in an L2 classroom. Thus, findings of this study have implications for language educators, curriculum designers, and policymakers, offering valuable insights and practical recommendations for integrating process drama in L2 teaching methodologies in diverse educational settings. Additionally, this research contributes to the ongoing discourse on innovative language teaching techniques, catering to the needs of the diverse student populations in language classroom. © 2023 Sciedu Press. All rights reserved.